Seed and microsite limitations of large-seeded, zoochorous trees in tropical forest restoration plantations in northern Thailand - Hathai A. Sangsupan (2018)
© 2018 On deforested or degraded land, planting mixtures of native forest tree species facilitates establishment of incoming tree seedling species (species recruitment) by rapidly re-establishing canopy cover. However, delayed colonization of plantations by large-seeded, zoochorous (LSZ) tree species can affect the species composition, structure, and function of the d eveloping forest. The objective of this study was to investigate whether microsites limit establishment (germination and early seedling survival) of LSZ tree species in three 13-year-old, seasonally dry, tropical forest restoration plantations in northern Thailand. We conducted a seed sowing experiment that combined five LSZ tree species with four microsite treatments in a split-plot design. All five tree species were previously absent from the understory of the plantations, despite seed sources being present in nearby natural forest. The four treatments simulated potential microsites that naturally-dispersed seeds may encounter. They included seed deposition on the surface of soil and on leaf litter, as well as seed burial beneath soil and beneath leaf litter. We fenced the experimental areas to prevent seed predation and focus on the environmental effects of microsites on the different stages of seedling establishment. Following seed sowing, we measured germination and seedling survival, mean height, and stem diameter over 26 months. The microsites treatments did not significantly affect germination and seedling survival, providing strong evidence that establishment of the tested species was not limited by the applied microsite environments. Furthermore, although there were significant differences in germination and survival among species, relatively high overall germination (37%) and 26-month seedling survival (58.5%), irrespective of microsite treatment, suggested that environmental conditions in the 13-year-old plantations generally met the requirements for germination and early seedling establishment. Microsite treatments also did not correlate with seedling height or stem diameter at 20 months, suggesting that initial germination microsites have no effect on seedling growth and robustness. Taken together, the results of this investigation support the hypothesis that seedlings of LSZ tree species are slow to colonize tropical forest restoration plantations because of seed limitations resulting from inadequate seed dispersal or low seed availability. The successful establishment of LSZ seedlings from sown seeds in this experiment suggests that direct seeding beneath the canopy of restoration plantations may be an effective way to offset seed dispersal limitations in restoration plantations. Furthermore, the absence of microsite treatment effects suggests broadcast sowing of seeds may be a simple way to recolonize closed-canopy restoration plantations with LSZ tree species.